Displacement-Based Framework for Simplified Seismic Loss Assessment - O'Reilly, Gerard J.; Monteiro, Ricardo; Nafeh, Al Mouayed Bellah; Sullivan, Timothy J.; Calvi, Gian Michele (Journal of earthquake engineering : JEE, 2020)
Loss assessment methodologies have been introduced to assess the seismic performance of buildings using more meaningful metrics like direct monetary losses. Different approaches exist, each with varying degrees of complexity and requiring different levels of detail, regarding structural behaviour characterisation or damage and loss estimation, for example. With these developments, loss assessment is increasingly becoming a more commonplace instrument in the seismic evaluation and retrofitting of existing buildings. Despite these developments, there is arguably still a need to provide practising engineers with simplified tools with which to conduct building-specific loss assessment. Displacement-based methodologies have been developed over the past number of years with a particular focus on design. The extension of this approach to loss assessment via displacement-based assessment (DBA) is the subject of this article, where a general framework for its implementation to different structural typologies is outlined and illustrated. This forms a general overview of a recently-concluded 5-year research project on the topic in Italy, where different research groups from various universities focused on specific building typologies as part of a coordinated effort to develop DBA for simplified loss assessment. An overview of the DBA method employed is presented here in addition to an overall description of the results of each working group. A summary of the developments for each typology examined is presented along with an illustration of the potential benefits of different retrofitting techniques in reducing monetary losses, whose details are found in the different typology-specific contributions to the special issue in which this paper is presented. To conclude, a comparative implementation of these simplified methodologies is described for three school buildings in Italy.